2021
DOI: 10.5433/1679-0359.2021v42n3p1159
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Brazilian distillers dried grains with solubles for pigs

Abstract: The purpose of this study was to evaluate the performance, carcass, meat and economic viability characteristics of pigs fed Brazilian coproducts of corn ethanol production. A total of 40 finishing pigs were subjected to four levels of distillers dried grains with solubles (DDGS; 0, 100, 200, or 300 g kg-1) for 28 days, and body weight, daily feed intake, daily weight gain and feed conversion were measured. After slaughter, the carcass yield, fat thickness, loin eye area, the depth and perimeter of the loin eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
5
1
1
Order By: Relevance
“…Studying 65-85 kg pigs,Corassa et al (2021) showed that inclusion up to 200 g kg -1 DDGS did not affect performance and carcass, suggesting that heavier pigs better support diets with DDGS when compared to the results of the present study. The reduction of performance based on the fiber content present in the DDGS is, according toBurrough et al (2015), due to increases in the insoluble fiber content, with the potential to affect the bacterial population in the colon.The costs of each kilogram of feed were RD R$ 0.4724 kg -1 feed; RD + PHY R$ 0.4811 kg -1 feed; DDGS R$ 0.4305 kg -1 feed; and DDGS + PHY R$ 0.4393 kg -1 feed (exp.…”
contrasting
confidence: 52%
See 2 more Smart Citations
“…Studying 65-85 kg pigs,Corassa et al (2021) showed that inclusion up to 200 g kg -1 DDGS did not affect performance and carcass, suggesting that heavier pigs better support diets with DDGS when compared to the results of the present study. The reduction of performance based on the fiber content present in the DDGS is, according toBurrough et al (2015), due to increases in the insoluble fiber content, with the potential to affect the bacterial population in the colon.The costs of each kilogram of feed were RD R$ 0.4724 kg -1 feed; RD + PHY R$ 0.4811 kg -1 feed; DDGS R$ 0.4305 kg -1 feed; and DDGS + PHY R$ 0.4393 kg -1 feed (exp.…”
contrasting
confidence: 52%
“…Thus, it is necessary to know the availability of nutrients and energy of these coproducts for a more precise formulation (Adeola & Kong, 2014), as they characterize the effects on animal performance and economic viability. Meanwhile, there is very little information about the nutritional value of DDGS produced in Brazil (Corassa et al, 2017(Corassa et al, , 2021. The presence of phytic acid in cereal products has limited the use of all nutrients by animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-two papers featuring nine different countries-Brazil [21], Bulgaria [22], Cuba [23], Egypt [24][25][26][27][28], Hungary [29], India [30,31], Philippines [32], Portugal [33], and the United States [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]-comprised the cost-benefit section of the review.…”
Section: Cost-benefit Analysismentioning
confidence: 99%
“…Com enorme potencial de substituição aos ingredientes tradicionais, os coprodutos de etanol de milho podem reduzir custos e otimizar formulações de rações para cadeias produtivas como a suinocultura brasileira, a quinta maior do mundo (ABPA, 2019) entretanto, pouquíssimos estudos com coprodutos do Brasil foram realizados (Corassa et al, 2017(Corassa et al, , 2019(Corassa et al, , 2021.…”
Section: Introductionunclassified